PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMK MUHAMMADIYAH 2 PALEMBANG - Nurul Mardiyyah Pratiwi (MANAJEMEN DEWANTARA, 2025)
Teacher performance is the result of work, both in quality and quantity, achieved by an individual in performing tasks in accordance with the responsibilities assigned to him/her. Factors that influence teacher performance are work environment, organizational culture, leadership, work motivation, work discipline, salary and job satisfaction. This study aims to determine whether there is a partial and simultaneous influence of work discipline and work environment on teacher performance at SMK Muhammadiyah 2 Palembang. The sampling technique used is the saturated sample technique, that is, all members of the population are sampled, while the sample in this study amounted to 50 people. This research method is a quantitative method with verification data analysis method. The results of the study partially show that work discipline has a significant effect on teachers' performance, work environment has no significant effect on teachers' performance, simultaneously work discipline and work environment together have a simultaneous effect on teachers' performance. Based on the coefficient of determination, it shows that work discipline and work environment can explain the variable of teacher performance by 38.2%.